ISLAMIC TRADITIONAL MANUSCRIPT IN THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Sofyan Sofyan; Hasan Asari; Al Rasyidin (JURNAL TARBIYAH, 2019)
This study focuses on the position of the traditional Islamic book (kitab kuning) as academic reference at Sharia and Law Faculty (FSH) and the Theology and Islamic Studies Faculty of State Islamic University of North Sumatra (Medan). The discussion will be elaborated into four problems of the study, namely: 1) How is the traditional Islamic book (kitab kuning) as academic reference in syllabus?; 2) How is the traditional Islamic book (kitab kuning) as academic reference in lecturers’ book teaching?; 3) How is the traditional Islamic book (kitab kuning) used in teaching and learning process?: 4) How is the traditional Islamic book (kitab kuning) as academic reference among students of Sharia and Law Faculty (FSH) and Theology and Islamic Studies Faculty (FUSI)? This study uses qualitative method with data collection which covers the interview, observation, and a documentary study. The data analysis was conducted on Miles and Huberman. The study concludes that the traditional Islamic book (kitab kuning) was used as scientific reference in syllabus and lecturers’ book teaching. In teaching and learning process, the traditional Islamic book (kitab kuning) was used as reference but many students did not read and understand it. It is due to their educational background commonly from public schools. In addition, most of the students used the traditional Islamic book (kitab kuning) as reference in their thesis. Traditional Islamic book (kitab kuning) that was used as academic reference including tauheed, Fiqh (Islamic Jurisprudence), tafseer (exegesis), ḥadiṡ (Prophet Muhammad’s words), ‘Ulūmul Qur’ān and ‘ulūmul  ḥadīṡ.